The Impact of Mountain Semeru's Eruption on Groundwater Resources in the Rejali Watershed in 2021 - Aulia Agustin Qurotulayun; Riyanto Haribowo; Abu Bakar Sambah (Universitas Diponegoro, 2023)
Mount Semeru is an active volcano and the highest on the island of Java with an altitude of 3726 meters above sea level (masl). The last major activity of Mount Semeru which occurred on 04 December 2021, there was an eruption or Hot Cloud Fall (GAP). According to the Centre for Volcanology and Geological Hazard Mitigation (PVMBG, 2021), the GAP in this incident was directed towards the southeast of Mount Semeru, namely Curah Kobokan with a glide distance of up to 11 km. The area affected by GAP is a small part of Malang Regency and Lumajang Regency. The purpose of this study is to analyze the quality of groundwater resources in the Rejali watershed after the eruption of Mount Semeru in 2021. This type of research is quantitative research. All data obtained is processed using the Pollution Index (IP) method listed in the Decree of the Minister of Environment Number: 115 of 2003 concerning Guidelines for Determining Water Quality Status. The groundwater quality parameters used are pH, BOD, DO, TDS, Fe, Mn, TSS, and COD. The results of this study are, the pollution index value in segments 1-3 is moderately polluted, and in segments 4-5 is lightly polluted.